2019
DOI: 10.1055/s-0039-1679868
|View full text |Cite
|
Sign up to set email alerts
|

Timely Data for Targeted Quality Improvement Interventions: Use of a Visual Analytics Dashboard for Bronchiolitis

Abstract: Background Standard methods for obtaining data may delay quality improvement (QI) interventions including for bronchiolitis, a common cause of childhood hospitalization. Objective To describe the use of a dashboard in the context of a multifaceted QI intervention aimed at reducing the use of chest radiographs, bronchodilators, antibiotics, steroids, and viral testing in patients with bronchiolitis. Methods This QI initiative took place at Children's Minnesota, a large, not-for-profit ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 44 publications
(61 reference statements)
0
33
0
Order By: Relevance
“…Of these studies, 56% (5/9) of the studies were deployed and evaluated in real-world hospital environments, and 44% (4/9) of the studies were conducted in controlled laboratory settings. The evaluation study duration ranged between 2 months [ 23 ] and 42 months [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 56% (5/9) of the studies were deployed and evaluated in real-world hospital environments, and 44% (4/9) of the studies were conducted in controlled laboratory settings. The evaluation study duration ranged between 2 months [ 23 ] and 42 months [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have developed visual analytics solutions that show timely and relevant clinical data, as well as the patterns found within them, which can be used for targeting patient and/or quality improvement interventions. [16][17][18] These visual analytics solutions often require a significant amount of effort to be put toward data integration and information management, 19 and their effectiveness on improving patient outcomes is unknown in the early stages of deployment and use. 17 More importantly, these visual analytics solutions are subject to potential humancomputer interaction (HCI) and usability issues resulting from the complicated interplay between human cognition and system functionality.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hester et al have demonstrated that providing integrated visual information for care of patients with bronchiolitis in the ED led to improvement in certain workflow metrics such as reduced length of stay. 33 A design issue highlighted by the analysis was that the timeline view did not appropriately signal changes in vital signs when values were outside of the plot boundaries (e.g., were too high or too low to fit on the screen). Off screen values were shown at the boundary (top or bottom) and were animated (flashed), but were connected to previous values with dashed lines and therefore did not indicate the degree of change using the salient feature of slope.…”
Section: Discussionmentioning
confidence: 99%